Exploring the SARS-CoV-2 structural proteins for multi-epitope vaccine development: an in-silico approach. (1st September 2020) - Kumar, Amit; Kumar, Prateek; Saumya, Kumar Udit; Kapuganti, Shivani K.; Bhardwaj, Taniya; Giri, Rajanish
ABSTRACT: Introduction: The ongoing life-threatening pandemic of coronavirus disease 2019 (COVID-19) has extensively affected the world. During this global health crisis, it is fundamentally crucial to find strategies to combat SARS-CoV-2. Despite several efforts in this direction and continuing clinical trials, no vaccine has been approved for it yet. Methods: To find a preventive measure, we have computationally designed a multi-epitopic subunit vaccine using immuno-informatic approaches. Results: The structural proteins of SARS-CoV-2 involved in its survival and pathogenicity were used to predict antigenic epitopes. The antigenic epitopes were capable of eliciting a strong humoral as well as cell-mediated immune response, our predictions suggest. The final vaccine was constructed by joining the all epitopes with specific linkers and to enhance their stability and immunogenicity. The physicochemical property of the vaccine was assessed. The vaccine 3D structure prediction and validation were done and docked with the human TLR-3 receptor. Furthermore, molecular dynamics simulations of the vaccine-TLR-3 receptor complex are employed to assess its dynamic motions and binding stability in-silico . Conclusion: Based on this study, we strongly suggest synthesizing this vaccine, which further can be tested in-vitro and in-vivo to check its potency in a cure for COVID-19.